Health, illness, ethos and epimeleia: Hesiod: A fold of concern about body care. An archaeological proposal - Colombani, María Cecilia (Romanitas - Revista de Estudos Grecolatinos, 2025)
In this article, we will address the characteristics that the ethical-dietary concern takes in the work of Hesiod. For this, we will analyze the recommendations that suggest a concern for a dietary issue, which stresses the health-disease dyad, inscribed in the ethos understood as a way of living. We propose an archaeological approach, which implies thinking and moving through a thicket of knowledge and discourses that constitute an underlying discursive conglomerate, without constituting a determining element of subsequent emergencies. Once each of the topics has been analyzed, we will try to think about the scope of this incipient subjectifying babbling in order to discover its ethical scope, trace and reveal what Michel Foucault understands by “politics of existence”, address an archaic fold of what represents the “arts of existence.” Ultimately, we will delve into the Hesiodic corpus to rescue what we understand as a concern for a “wisdom of life”, to think about the relationships between myth and philosophy.